Involvement of Dopamine D2 Receptors in Addictive-Like Behaviour for Acetaldehyde - Brancato, Anna (Public Library of Science, 2014)
Acetaldehyde, the first metabolite of ethanol, is active in the central nervous system, where it exerts motivational properties. Acetaldehyde is able to induce drinking behaviour in operant-conflict paradigms that resemble the core features of the addictive phenotype: drug-intake acquisition and maintenance, drug-seeking, relapse and drug use despite negative consequences. Since acetaldehyde directly stimulates dopamine neuronal firing in the mesolimbic system, the aim of this study was the investigation of dopamine D2-receptors' role in the onset of the operant drinking behaviour for acetaldehyde in different functional stages, by the administration of two different D2-receptor agonists, quinpirole and ropinirole. Our results show that acetaldehyde was able to induce and maintain a drug-taking behaviour, displaying an escalation during training, and a reinstatement behaviour after 1-week forced abstinence. Acetaldehyde operant drinking behaviour involved D2-receptor signalling: in particular, quinpirole administration at 0.03 mg/kg, induced a significant decrease in the number of lever presses both in extinction and in relapse. Ropinirole, administered at 0.03 mg/kg during extinction, did not produce any modification but, when administered during abstinence, induced a strong decrease in acetaldehyde intake in the following relapse session. Taken together, our data suggest that acetaldehyde exerts its own motivational properties, involving the dopaminergic transmission: indeed, activation of pre-synaptic D2-receptors by quinpirole, during extinction and relapse, negatively affects operant behaviour for acetaldehyde, likely decreasing acetaldehyde-induced dopamine release. The activation of post-synaptic D2-receptors by ropinirole, during abstinence, decreases the motivation to the consecutive reinstatement of acetaldehyde drinking behaviour, likely counteracting the reduction in the dopaminergic tone typical of withdrawal. These data further strengthen the evidence that acetaldehyde may play a crucial role as mediator of ethanol's central effects.